Evaluating and Motivating Activation in Long Term Care: Lessons From a Pilot Study. Issue 1 (June 2021) - Jbilou, J.; El Bouazaoui, A.; Zhang, B.; Henry, J.L.; McDonald, L; Hall, T.; Chang, R.; Barton, D.; Chignell, M.H.
Older adults living in long-term care facilities typically receive insufficient exercise and have long periods of the day when they are not doing anything other than sitting or lying down, watching television, or ruminating (Wilkinson et al., 2017). We developed an intervention called the Experiential Centivizer, which provides residents with opportunities to use a driving simulator, watch world travel videos, and engage in exercise. We assessed the impact of the intervention on residents of a long-term care home in Fredericton, NB, Canada. In this paper, we report on the results observed and highlight the lessons learned from implementing a technological intervention within a long-term care setting. Practical and research recommendations are also discussed to facilitate future intervention implementation in long-term care.